PERAN PENGAWAS SEKOLAH DALAM PENINGKATAN MUTU PENDIDIKAN DI SDN 3 AIR SALEK - Kusrimah, Kusrimah (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstract— This research begins with conditions that indicate the low quality of education that is very worrying, even at the level of Southeast Asia we occupy the lowest position. The main problems of national education that need to be prioritized are four kinds of problems, namely the problem of educational equity, the problem of education quality, the problem of educational efficiency, and the problem of educational relevance (Hartono, 2011). Improving the quality of education through quality supervision is the process of overseeing efforts to improve the quality of education units by LPMP together with school supervisors. The purpose of quality supervision for schools are to improve the quality of their education through the implementation of an internal quality assurance system (SPMI), the implementation of PPK, literacy, and the implementation of the 2013 curriculum towards the realization of quality culture schools. This research was conducted at SDN 3 Air Salek with a descriptive qualitative research with data collection techniques in the form of documentation observation and interviews. The results showed the role of school supervisors as well as being a supervisor also carried out mentoring activities in improving quality in schools.Keywords— Improving the quality, The role of school supervisors, SDN 3 Air SalekAbstrak— Penelitian ini berawal dari kondisi yang menunjukkan rendahnya mutu pendidikan yang sangat mengkhawatirkan, bahkan di tingkat Asia Tenggara kita menempati posisi terendah. Permasalahan pokok pendidikan nasional yang perlu diprioritaskan penanggulangannya ada empat macam, yaitu masalah pemerataan pendidikan, masalah mutu pendidikan, masalah efisiensi pendidikan, dan masalah relevansi pendidikan (Hartono, 2011). Peningkatan mutu pendidikan melalui supervise mutu adalah proses mengawal upaya peningkatan mutu pada satuan pendidikan oleh LPMP bersama pengawas sekolah. Tujuan supervisi mutu adalah agar sekolah meningkat mutu pendidikannya melalui penerapan system penjaminan mutu internal (SPMI), pelaksanaan PPK, literasi, dan pelaksanaan kurikulum 2013 menuju terwujudnya sekolah berbudaya mutu. Penelitian ini dilaksanakan di SDN 3 Air Salek dengan jenis penelitian kualitatif deskriptif dengan teknik pengumpulan data berupa observasi dokumentasi dan wawancara. Hasil penelitian menunjukkan peran pengawas sekolah selain sebagai supervisor juga melaksanakan aktifitas pendampingan dalam peningkatan mutu di sekolah.Kata Kunci— peningkatan Mutu, Peran Pengawas Sekolah, SDN 3 Air Salek